A Theory of Dramaturgy - Szatkowski, Janek (Routledge, 2019)
A Theory of Dramaturgy is the first text of its kind to define concepts and combine arguments into a coherent dramaturgical theory supported by an operative systems theory. This is a wide-ranging theory with historical and contemporary perspectives on dramaturgy, rather thansimply a how-to book. Dramaturgy began in ancient Greece, born from experimentation with democracy and commentary in the theatre on the human condition. The term itself has seen constant evolution, but thanks to its introduction into common English usage within the last three decades, it has gained new importance. Dramaturgy draws focus to the communication of communication, and in theatre it examines how moving bodies, voice, sound, and light can tell a story and affect values. Beyond the theatre, in daily life, dramaturgy becomes a question of "performativity", as we constantly have to act in relation to the roles that we occupy. It is because of this that the way in which society describes itself to itself is not just a matter for scientists and theorists, but for all of those who are met on a daily basis with devised, staged, and directed versions of important values and events in our contemporary lives. Ideal for both scholars and students, A Theory of Dramaturgy explains how to approach the values, strategies, and theories that are essential to understanding arts and media, and investigates what art should do in the current world.- Resumé vydavatel
Keywords: divadelní dramaturgie; dramaturgy; elektronické knihy; monografie; electronic books; monographs